2022
DOI: 10.1159/000525572
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo and in vitro Monocyte Responses Do Not Reflect in vivo Immune Responses and Tolerance

Abstract: Cytokine production by ex vivo (EV)-stimulated leukocytes is commonly used to gauge immune function and frequently proposed to guide immunomodulatory therapy. However, whether EV cytokine production capacity accurately reflects the in vivo (IV) immune status is largely unknown. We investigated relationships between EV monocyte cytokine responses and IV cytokine responses in a large cohort of healthy volunteers using a highly standardized IV model of short-lived LPS-induced systemic inflammation, which captures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Based on the finding that plasma cytokine concentrations are attenuated by CytoSorb treatment, while the development of immunological tolerance is not, we speculate that tolerance must be rapidly induced in tissue-resident immune cells by locally produced cytokines before these cytokines even reach the circulation. Earlier work from our group demonstrated a complete lack of correlation between circulating cytokine concentrations and ex vivo cytokine production capacity of immune cells ( 6 , 13 ), thereby implying that the contribution of circulating leukocytes to blood cytokine concentrations and immunological tolerance following LPS administration is very limited, also illustrates the relevance of tissue-resident macrophages. However, it needs to be acknowledged that a role for endothelial cells cannot be ruled out, as these are known cytokine producers ( 27 , 28 ) and may be rapidly reprogrammed to a tolerant phenotype upon contact with cytokines that enter the circulation from the tissues.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Based on the finding that plasma cytokine concentrations are attenuated by CytoSorb treatment, while the development of immunological tolerance is not, we speculate that tolerance must be rapidly induced in tissue-resident immune cells by locally produced cytokines before these cytokines even reach the circulation. Earlier work from our group demonstrated a complete lack of correlation between circulating cytokine concentrations and ex vivo cytokine production capacity of immune cells ( 6 , 13 ), thereby implying that the contribution of circulating leukocytes to blood cytokine concentrations and immunological tolerance following LPS administration is very limited, also illustrates the relevance of tissue-resident macrophages. However, it needs to be acknowledged that a role for endothelial cells cannot be ruled out, as these are known cytokine producers ( 27 , 28 ) and may be rapidly reprogrammed to a tolerant phenotype upon contact with cytokines that enter the circulation from the tissues.…”
Section: Discussionmentioning
confidence: 90%
“…The goal of this proof-of-principle study was to investigate whether the CytoSorb device is capable of attenuating plasma cytokine concentrations after induction of systemic inflammation. Previous endotoxemia studies have demonstrated that several cytokines already start to increase within 30 min after LPS administration (6). Therefore, CytoSorb hemoperfusion was initiated fifteen minutes after the initial LPS bolus to maximize the chances of demonstrating a treatment effect.…”
Section: Cytosorb Hemoperfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Evidence supporting the rationale for this study comes primarily from in vitro studies, experiments in healthy individuals, and observations from uncontrolled case series suggesting effective IL-6 adsorption by the adsorption device. 11 40 However, several independent clinical trials have questioned this expectation. In recent randomized controlled trials, no significant reduction of ILs by use of cytokine adsorption in various clinical settings could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a larger cohort study performed at the department of Intensive Care Medicine of Radboudumc in Nijmegen, the Netherlands, which aimed to identify genomic and transcriptomic biomarkers of interindividual variability in acute systemic inflammation and immune tolerance in vivo (Jansen et al, 2022). In this study, we recruited 113 healthy, non-smoking Caucasian participants aged between 18 and 30 years who had no medical/psychiatric history and did not use prescription drugs (see Supplementary Table S1 for inclusion and exclusion criteria).…”
Section: Study Design Participants and Ethicsmentioning
confidence: 99%